Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Anggota Koperasi Persaudaraan Harmonis Syariah Bonang Tangerang Banten - Aisyah Defy R. Simatupang; Sri Deti (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2021)
This study aims to see how much influence the quality of employee service has on the satisfaction of members of the Sharia Harmonious Brotherhood Cooperative. The data used were obtained from questionnaire data that were distributed to Kopernis members. Determination of sample using purposive sample found 60 samples. The data analysis method is multiple linear regression and the hypothesis testing is simultaneous test (F test), partial test (T test) and determination coefficient test (R2). The data was processed using SPPS version 22. The multiple regression test in this study is: Y = 4,832 + 570 X1 + -186 X2 + 204 X3 + 458 X4 + -230 X5 + 070 X6. From the calculation of the simultaneous F test, it is obtained 11,957 (sig value 0,000 <0.05, which means that there is a significant influence between CARTER and member satisfaction. Meanwhile, the partial test results (t) show that the variables of Sharia Compliance and Tangibles have a significant positive effect on the satisfaction of members of the Harmonious Brotherhood Cooperative. Sharia, while the variables of Assurance, Reliability, Empathy and Responsiveness do not have a significant effect on the satisfaction of the members of the Bonang Syariah Harmonious Brotherhood Cooperative, seen from the results of the determination test (R2) is 0.575.